Failure of talc seromadesis for the treatment of subcutaneous chronic seromas after incisional hernia surgery. (March 2021) - Lopez-Monclus, J.; Artes, M.; Gonzalez, J.; Blazquez, L. A.; Lucena, J. L.; Robin, A.; Munoz, J. M.; San-Miguel, C.; Garcia-Urena, M. A.
Background and Aim: Talc poudrage has been used since many years for sclerosing chronic pleural effusion. Several reports have shown good results managing chronic seromas after breast, vascular, and incisional hernia surgeries. The purpose of this study is to determine the utility of talc seromadesis for the management of chronic seromas after incisional hernia surgery Materials and Methods: Multicentric prospective observational study including patients diagnosed of chronic seromas after incisional hernia surgery. Under local anesthesia and ultrasonographic control, two percutaneous trocars were placed in the seroma, washing the seroma cavity with 0.9% saline solution and aspirating the remaining liquid. A sample of 4 g of talcum powder was introduced in the seroma cavity, and a 15-F drain was left in place. Patients were followed each week during at least 4 weeks after drainage removal. Results: Between January 2013 and December 2016, a total of six patients were enrolled in the study. Talc poudrage was performed without any complications. Drains were pulled out in a mean time of 3 (range: 2–4) weeks. One case of the chronic seromas was efficiently sclerosed with talc without recurrence in time. In three cases, the seroma recurred, and the final solution was surgical decortication of the seroma. In the other two cases, seroma also recurred and were managed with instillation of ethanol and iodine povidone. Conclusion: In our experience, the management of chronic seromas after incisional hernia repair with talc seromadesis is ineffective and is associated with a high rate of seroma recurrence.